2010
DOI: 10.1002/jcc.21483
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of the full catalytic cycle for the propene hydroformylation catalyzed by a heterobimetallic HPt(SnCl3)(PH3)2 model catalyst

Abstract: DFT calculations were carried out to study the full catalytic cycle for the hydroformylation of propene, catalyzed by the heterobimetallic model catalyst trans-Pt(H)(PH(3))(2)(SnCl(3)). Before the study of the full catalytic cycle, the performance of six pure GGA, one GGA with inclusion of dispersion corrections, four hybrid-GGA, and three meta-GGA exchange correlation functional to describe a model reaction promoted by Pt-Sn catalyst were assessed. It is shown that the BP86 and GPW91 functionals, using extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…142 Whether the olefin insertion or the subsequent carbonylation is the regiochemistry determining step is still under discussion. 143,144 In the early 1970s Clark and Kurosawa intensively investigated the mechanism of the stoichiometric and catalytic isomerization of terminal and internal olefins (1-butene, allyl ethers) with phosphine-modified platinum hydrido complexes of the type trans-[HPt(PR 3 ) 2 (acetone)]X and trans-[HPt-(ClO 4 )(PPh 3 ) 2 ]. 145 Later on, Toniolo et al showed that the isomerization rate is strongly dependent on the temperature.…”
Section: ■ Platinum Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…142 Whether the olefin insertion or the subsequent carbonylation is the regiochemistry determining step is still under discussion. 143,144 In the early 1970s Clark and Kurosawa intensively investigated the mechanism of the stoichiometric and catalytic isomerization of terminal and internal olefins (1-butene, allyl ethers) with phosphine-modified platinum hydrido complexes of the type trans-[HPt(PR 3 ) 2 (acetone)]X and trans-[HPt-(ClO 4 )(PPh 3 ) 2 ]. 145 Later on, Toniolo et al showed that the isomerization rate is strongly dependent on the temperature.…”
Section: ■ Platinum Catalystsmentioning
confidence: 99%
“…Frequently, this problem has been overcome by use of styrenes as model substrates, which direct the hydroformylation to the position next to the aryl ring . Whether the olefin insertion or the subsequent carbonylation is the regiochemistry determining step is still under discussion. , …”
Section: Platinum Catalystsmentioning
confidence: 99%
“…A fõbb elemi lépések megegyeznek, függetlenül attól, hogy a katalizátor kobalt, 14 ródium, 15 vagy platina 16 központi atomra épül (2. Ábra).…”
Section: áBra a Hidroformilezési Reakció Etilén (A) Aromás Olefinekunclassified